The Impact of Remittance Inflows on Economic Growth: Evidence from Asian Countries - Very Budiyanto; Wasiaturrahma Wasiaturrahma; Wisnu Wibowo (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: The originality of this research stems from its extended observation period, the inclusion of detailed macroeconomic control variables, and the analysis of both immediate and sustained effects of remittances on economic growth. Research Objectives: This study aims to analyze the impact of remittances on economic growth in 22 Asian countries over the period 2004–2023. Research Methods: This study employs a panel data approach using the Generalized Method of Moments (GMM) to address econometric issues such as endogeneity and unobserved heterogeneity, while incorporating variables including foreign direct investment, inflation, population growth, education, household consumption, government expenditure, and exports. Empirical Results: The findings indicate that remittances have a positive effect on economic growth in both the short- and long-run. However, the short-run impact is not always statistically significant. Exports and inflation show positive effects, whereas foreign direct investment and education show negative effects in some specifications. Implications: These results suggest that remittances play an important role as a complementary source of development financing in Asian economies, and policymakers should encourage their productive use to strengthen sustainable economic growth. JEL Classification: F24, O11, C23, E31 How to Cite:Budiyanto, V., Wasiaturrahma., & Wibowo, W. (2026). The Impact of Remittance Inflows on Economic Growth: Evidence from Asian Countries. Signifikan: Jurnal Ilmu Ekonomi, 15(2), 407-xx. https://doi.org/10.15408/sjie.v15i2.50455.